(untitled) (Bangladesh Agronomy Journal, 2021)
The experiment was conducted at the research field of the Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Gazipur and Regional Agricultural Research Stations (RARS), Burirhat during two successive rabi seasons of 2015 and 17 to find out the relation between different development events of garden pea (Pisum sativum L.) and the sowing time based temperature, and also to minimize the yield reduction by adopting appropriate management practices. The treatments comprised with three sowing dates (30 November, 15 December and 30 December) and three management practices (low, medium and high). Under high management, Nov. 30 sowing took maximum days (64 days in 2015-16 and 58 days in 2016-17 at Joydebpur and 58 days in 2015-16 and 57 days in 2016-17 at RARS, Burirhat) to reach harvesting maturity. The results indicated that the number of days required for attaining different phenological stages decreased with delay of sowing. Late sowing took minimum time from flowering to fresh pod maturity (51 days and 49 days in two years at Joydebpur, and 49 days and 46 days in two years at Burirhat) due to increase in minimum temperature. The results revealed that the highest pod yield (14.77 t ha-1in 2015-16 and 13.09 t ha-1in 2016-17 at Joydebpur and 9.63 tha-1 in 2015-16 and 10.33 t ha-1in 2016-17 at Burirhat) was recorded from 30 November sowing with high management practices which was followed by 15 December with the same management. Yield reduction in late sowing was reduced to some extent by high management practices. The two year results revealed that 30 November sowing with high management practices (extra 20% recommended fertilizer dose, HRC + two irrigation at pre flowering and pod development stage + seed treatment + one weeding at 21 DAE) showed better pod yield than other combinations. Bangladesh Agron. J. 2020, 23(2): 13-22